Diagnostic accuracy between fine needle aspiration biopsy (FNA) and pathological examination of the thyroid - Jerso Menegassi; Vanessa Bordin; Saimon Santos Oliveira (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Despite the fact that the fine needle aspiration biopsy (FNA) is commonly used in the initial evaluation and distinction of benign and malignant lesions of thyroid nodules, it may yield variable results, inasmuch as it is contingent on the pathologist's analysis and expertise in collecting appropriate samples. OBJECTIVE: To check the diagnostic accuracy between FNA and pathological examination of thyroid nodules, both performed in a diagnostic pathology service. METHODS: Retrospective study carried out in a diagnostic pathology service in Chapecó, Santa Catarina, Brazil. All patients who underwent FNA and pathological examination in the period from January 1st 2005 to December 31 2010 were included in this study. RESULTS: 1,172 FNA were conducted during this period and 265 patients underwent both FNA and pathological examination. Most patients were female (85%), with mean age 47.75 years (standard deviation [SD] = 14.93 years). Cytopathological examinations yielded the following results: benignity (43.77 %), suspected malignancy (23.77%), follicular neoplasm (5.28%), atypical follicular lesion of undetermined significance (1.51%) and unsatisfactory sample (1.51%). In the pathological examination, the most predominant diagnoses were colloid goiter (38.87%), follicular adenoma (22.64%) and classic papillary carcinoma (18.87%). In satisfactory samples (n = 261), the following results were obtained: diagnostic accuracy (89.66%), sensitivity (82.14%), specificity (93.22%), negative predictive value (91.67%) and positive predictive value (75.19%). CONCLUSION: We concluded that FNA provides a good predictive value for benign thyroid, constituting a reliable and effective tool for diagnosis and surgical indication.